Pengaruh Kegiatan Mozaik Terhadap Kemampuan Motorik Halus Anak Usia 5-6 Tahun - Anugrah, Suci; Muhammad Yusri Bachtiar; Muhammad Akil Musi; Rika Kurnia R; Halifah, Syarifah (Anakta : Jurnal Pendidikan Islam Anak Usia Dini, 2023)
Based on initial observations made by researchers in October 2022 at TK Aisyiyah Bustanul Athfal Cakke, there were 12 children, consisting of 7 girls and 5 boys. It can be seen that the child's fine motor skills are still low. The low fine motor skills of children include being unable to move their fingers, such as in cutting and pasting activities children still cannot hold scissors and stick neatly. Lack of eye coordination with hands, children focus less on cutting and pasting activities. And less able to coordinate fingers flexibly when holding objects such as in cutting and pasting activities. It is known that the purpose of this research is to see the effects/impacts of mosaic activities carried out with origami paper. The method used is known to be a quantitative research with a quasi-experimental design. The research findings lead us to the conclusion that the fine motor skills/skills in the experimental group were superior to the control group when they participated in the Mosaic activity involving origami paper and green bean seeds. The experimental group experienced an average increase of 20.66 percent, while the control group experienced a 1.5 percent decrease, according to an analysis of the data. Significant value can be seen in the test results. 2-tailed 0.026 0.05 , H1 is accepted while HO is not accepted. So it can be concluded that Aisyayiah Bustanul Athfal Kindergarten children from group B Cakke's fine motor skills were significantly influenced by mosaic activities involving borigami paper and green bean seeds.